Pancreatic lipase inhibition of strictinin isolated from Pu'er tea (Cammelia sinensis) and its anti-obesity effects in C57BL6 mice. (September 2018) - Chen, Tzu-Yin; Wang, Miki M.C.; Hsieh, Sheng-Kuo; Hsieh, Meng-Huang; Chen, Wen-Ying; Tzen, Jason T.C.
Graphical abstract: Highlights: Effective inhibition of strictinin on pancreatic lipase in vitro . Reducing the blood triglyceride level of mice via administration of strictinin. Lowering fat accumulation in mice fed with high-fat diet by supplying strictinin. Abstract: Strictinin isolated from Pu'er tea was demonstrated to inhibit pancreatic lipase in vitro . In an olive oil tolerance test, the administration of strictinin (100 mg/kg) significantly reduced the blood triglyceride level and increased the fecal oil content of C57BL6 mice. In a long-term animal study, the body weight gained via high-fat diet was significantly reduced in the mice supplemented with strictinin of 130 mg/kg. Further analysis showed that weight of epididymal fat, but not that of liver or muscle, increased in mice fed with high-fat diet, and the increase of fat was reduced in the mice supplemented with strictinin. Correspondingly, sizes of adipocytes in epididymis were substantially enlarged in mice fed with high-fat diet, and the enlargement of adipocytes was decreased when strictinin was supplemented. Levels of blood triglyceride, cholesterol and glucose were elevated in mice fed with high-fat diet, and these elevated levels were reduced when strictinin was supplemented.